Characterization of Zn-doped CuSCN Nano-powders synthesized via an in situ method for enhanced optical and structural properties - Enas Abdullah Al-Mahdi; A.M. Abdulwahab; Adnan Alnehia; Ahmed AL-Osta; Abdel-Baset Al-Odayni (Results in Chemistry)
This study investigates the influence of zinc doping on the physical properties of copper thiocyanate (CuSCN) nanopowders synthesized using an in situ method. Pure and zinc-doped CuSCN nanopowders were synthesized and characterized through a multi-technique approach, including scanning electron microscopy (SEM), UV–visible spectrophotometry, X-ray diffraction (XRD), electrical measurements, and antibacterial assays. XRD analysis confirmed the rhombohedral structure of all samples, with a slight increase in crystallite size observed in zinc-doped samples (1 % to 7 %) from 39.46 nm to 41.84 nm. The synthesized nanopowders exhibited antibacterial activity against both P. aeruginosa and S. aureus. Optical characterization revealed a decrease in both direct and indirect optical band gap energies with increasing zinc content. Furthermore, Zn doping resulted in an enhancement in the dc electrical conductivity of CuSCN. These findings suggest that zinc doping can improve the optoelectronic properties of CuSCN, making it a promising candidate for applications such as hole transport layers (HTLs) in solar cell devices.